Investigation of Pseudomonas biofilm development and removal on dairy processing equipment surfaces using Fourier transform infrared (FT-IR) spectroscopy - Manuzon, Michele Yabes (Ann Arbor Michigan ProQuest LLC, 2009)
Biofilms pose a significant concern in the food industry since they could contaminate food products with pathogenic and spoilage microorganisms. Their complete removal from processing equipment surfaces is highly desired to ensure the safety and quality of finished products. Pseudomonas spp. are among the most common spoilage agents of dairy, produce, and meat products. These organisms are usually found as part of biofilms in food processing equipment. Rapid methods that would allow the detection and identification of these microorganisms as well as the analysis of their biofilms would greatly benefit the food processing industry. In this study, methods based on Fourier transform infrared (FT-IR) spectroscopy were developed and evaluated for the identification of Pseudomonas spp. and also for the detection and rapid compositional analysis of their biofilms. FT-IR spectroscopy was also used to assess the efficiency of clean-in-place (CIP) system for biofilm removal. Results showed that FT-IR spectroscopy when coupled with soft independent modeling of class analogy (SIMCA) could differentiate Pseudomonas spp. from other bacterial genera and among closely-related strains. FT-IR technology also provided characteristic "fingerprint" spectral patterns which showed both major and subtle compositional changes in biofilms during their development. Partial least squares regression (PLSR) models using recovered biofilms showed that there was a good correlation between the FT-IR spectra and the viable cell counts in the biofilm. Evaluation of alkali treatment with and without sodium hypochlorite (NaOCl) showed that biofilm removal was not significantly improved upon NaOCl addition. The results of this study demonstrate the great potential of FT-IR spectroscopy and multivariate analysis for the rapid and reliable identification and discrimination of Pseudomonas spp. The developed technique could be used to identify and potentially enumerate Pseudomonas from mixed microbial populations on food processing surfaces and to monitor the contamination patterns of different spoilage strains in the processing environment. FT-IR spectroscopy also provides useful information on the nature of organic contaminants present on equipment surfaces. This technique could find wide applications in the food industry for the rapid detection and compositional analysis of biofilms on food processing equipment, and will be very useful for optimizing and monitoring the effectiveness of equipment cleaning procedures.--Abstract.
Thesis (Ph.D.)--Ohio State University, 2009.
Keywords: Pseudomonas; Biofilm; Fourier transform infrared spectroscopy